Linking servant leadership to followers' thriving at work: self-determination theory perspective - Jiang, Xiaoqun; Wei, Yiyi (Frontiers in psychology, 2024)
Previous studies have confirmed that servant leadership has a positive impact on thriving at work, however, the psychological mechanism in this process has not been fully understood. Based on Self-Determination Theory, this study examines the mediating effect of basic psychological needs and the moderating effect of power distance on the relationship between servant leadership and followers' thriving at work. The results from the between-subject experimental design (Study 1) indicate that servant leadership can satisfy followers' three basic psychological needs. And the results from a questionnaire survey of 455 civil servants at two-time points (Study 2) indicate: (1) Servant leadership has a significantly positive impact on followers' thriving at work; (2) All three basic psychological needs satisfaction serve as a mediator in the relationship between servant leadership and followers' thriving at work; (3) Power distance negatively moderates the relationship between servant leadership and the satisfaction of three basic psychological needs, meaning that the lower on the power distance, the stronger the positive relationship between servant leadership and the satisfaction of three basic psychological needs; (4) Power distance negatively moderates the mediating effects of competence needs satisfaction and relatedness needs satisfaction in the relationship between servant leadership and followers' thriving at work, indicating that the lower on the power distance, the stronger the mediating effects. Our findings highlight the important role of servant leadership in fostering followers' thriving at work and explore the critical role of basic psychological needs satisfaction. This provides empirical evidence to further refine theories regarding thriving at work, and suggests that in order to promote employee thriving, it is important to guide leaders to reevaluating and repositioning their roles.